Fabrication of polyvinyl alcohol/multi‐walled carbon nanotubes composite electrospun nanofibres and their application as microwave absorbing material. (1st August 2013) - Salimbeygi, Golestan; Nasouri, Komeil; Shoushtari, Ahmad Mousavi; Malek, Reza; Mazaheri, Firoozmehr
Abstract : Polyvinyl alcohol (PVA)/sodium dodecyl sulphate (SDS)/multi‐walled carbon nanotubes (MWCNTs) composite nanofibres with various MWCNT contents (up to 10 wt%) were fabricated by electrospinning process and their microwave absorption properties were evaluated by a vector network analyser in the frequency range of 8–12 GHz (X‐band) at room temperature. Scanning electron microscopy analysis of the nanofibre samples revealed that the deformation of the nanofibres increases with increasing MWCNT concentration. Very smooth surfaces of the composite electrospun nanofibres even for nanofibres with concentration of 10 wt% MWCNT have been successfully prepared because of the high stability dispersion of MWCNTs. It was observed that the absorption microwave properties improved by increasing the loading levels of MWCNTs. Finally, the PVA/SDS/MWCNT composite nanofibres sample with 10 wt% content of MWCNT has shown a reflection loss of 15 dB at a frequency of 8 GHz.